Inside the black box of a successful parent-infant intervention in a South African informal settlement : mothers' and counsellors’ accounts of the process - Landman, Mireille (Stellenbosch : University of Stellenbosch, 2009)
Thesis (DPhil (Psychology))—University of Stellenbosch, 2009.